Inverting the laparoscopic cholecystectomy: a case of acute biliary pancreatitis in situs inversus - Ahmad, Raheel; Shafique, Muhammad S.; Ahmad, Sheikh H.; Mehmood, Saqib; Khan, Jahangir S. (International Surgery Journal, 2017)
A 57-year-old female presented in Outpatient Department with complaints of left upper abdominal pain for last 5 days. She had left hypochondrial and epigastric tenderness with apex beat palpable in right 5th intercostal space. Diagnostic work-up revealed acute biliary pancreatitis with situs inversus totalis. Abdominal sonogram showed left sided distended gallbladder with multiple stones. Laparoscopic cholecystectomy was done after initial stabilization of the patient. Patient’s recovery was uneventful in the postoperative period.